Eficacia del vendaje neuromuscular como complemento de la terapia descongestiva compleja en pacientes con linfedema de extremidades inferiores relacionada con el cáncer Servicio de Medicina Física y Rehabilitación del Instituto Nacional de Enfermedades Neoplásicas - Cespedes Ramos, Ana María (2021)
Lower limb lymphedema is a frequent complication in patients treated for cancer, which negatively affects the quality of life of survivors. Aim: To determine the efficacy of Neuromuscular Taping (NT) as an adjunct to complex decongestive therapy (CDT) in patients with cancer-related lymphedema of the lower extremities. Material and methods: Pilot, experimental non-pharmacological study of parallel groups of randomized and open assignment. Patients with grade II and III lower limb lymphedema were included, in two groups of 15 participants each: CDT group (that received conventional therapy constituted by manual lymphatic drainage, intermittent sequential pneumatic pressotherapy, multilayer bandage, lymphokinetics exercises and care skin) and CDT+ NT group (that received conventional therapy + Neuromuscular Taping). Volume of the compromised lower limb was evaluated by circometry and variables such as joint range of motion, muscle strength, intensity of pain, heaviness and quality of life. Outcomes: The CDT + NT group significantly decreased their weight by 1.9 ± 1.5 kg, their BMI by 0.8 ± 0.6 kg / cm2 and significantly increased joint range of motion of the hip by 9 ° and ankle by 3 ° (p <0.05); however, we did not find statistically significant differences in the other variables, including the volume of the compromised lower limb. Conclusions: The results show that Neuromuscular Taping as a complement to CDT is not more effective than the standard method in the treatment of patients with grade II and III lymphedema lower extremity. However, a significant increase hip and ankle joint range of motion was found.